Platelet Rich Plasma in the Management of Recurrent Lumbar Disc Surgery; A Study of Ten Cases (Bangladesh Journal of Neurosurgery, 2024)
Low back pain (LBP) is a very common entity, now regarded as the first cause of disability worldwide. Intervertebral disc (IVD) degeneration leads to posterior rupture annulus fibrosus (AF) with extrusion of Central Nucleus pulposus (NP) through the injured area which has little potential to repair as it has no blood supply and causes mechanical pressure and inflammatory changes in the nerve root causing LBP. Autologous platelet rich plasma (PRP) contain concentrate blood that contain a natural concentration of autologous growth factors and cytokines and currently widely used in the clinical setting for tissue regeneration and repair. PRP had great potential to stimulate cell proliferation and metabolic activity of IVD effectively restoring structural change, improving matrix integrity, IVD regeneration, reducing discogenic back pain. Our Study of 10 cases, where repeat or re-exploration surgery (after primary PLID Surgery, fenestration and discectomy) was done, where removal of recurrent disc 5, release of epidural fibrosis and perineural scarring 4 and surgical debridement for discitis 1 was done. In addition, PRP was given in the disc space & around the nerve root which provides lots of growth factor, cytokines which helps in disc regeneration and prevent adhesion & fibrosis. These dual actions enhance symptomatic recovery of all cases. Large scale studies may be required to confirm the clinical evidence of PRP for the treatment of discogenic LBPBang. J Neurosurgery 2024; 13(2): 70-74